Regulatory mechanisms of exercise-induced physiological cardiac hypertrophy: progress and prospects - Cheng, Peng; Zhang, Xi; Si, Yi; Yin, Qiushi; Chen, Lin; Ru, Qin; Chu, Chong; Xiang, Hongyue; Liao, Ling; Ran, Hang; Zhang, Zaihong; Wu, Yuxiang (Frontiers in Cardiovascular Medicine, 2025)
IntroductionExercise-induced physiological cardiac hypertrophy (PCH) plays a significant role in cardiovascular health. Although substantial progress has been made in recent years, the precise regulatory mechanisms underlying this adaptive remodeling remain incompletely elucidated and warrant further investigation.MethodsThe literature retrieval and selection process in this study adhered to the PRISMA guidelines. Databases such as Web of Science, PubMed, Embase, and the Cochrane Library were searched, with the retrieval period covering from the establishment of the respective databases up to August 2025. Keywords used in the search included “exercise”, “physiological cardiac hypertrophy”, “assessment methods”, “regulatory mechanisms”, and “cardiovascular health”. Inclusion criteria were: (1) studies exploring the regulatory mechanisms or health effects of exercise on physiological cardiac hypertrophy; (2) studies involving healthy adults (≥18 years) or wild-type animal models (e.g., C57BL/6 mice); (3) studies employing quantitative imaging, laboratory, or electrophysiological methods to assess physiological cardiac hypertrophy. Exclusion criteria included studies focused solely on pathological cardiac hypertrophy, experimental studies lacking a control group, and studies assessed as having a high risk of bias. Literature selection was independently performed by two researchers, and the final eligible studies were systematically summarized.ResultsThis review first outlines the definitions, characteristics, and clinical evaluation methods of PCH. It then examines the impact of different exercise modalities on cardiac remodeling and summarizes the underlying regulatory mechanisms, including transcriptional pathways (e.g., IGF-1/PI3K/Akt, NRG1/ErbB signaling), post-transcriptional processes (e.g., RNA m6A methylation and noncoding RNA regulation), and metabolic adaptations (e.g., fatty acid oxidation and glucose utilization).The beneficial effects of exercise-induced physiological cardiac hypertrophy on cardiovascular health are also thoroughly analyzed.DiscussionDespite its benefits, several challenges remain. Distinguishing PCH from pathological cardiac hypertrophy (PMH) remains difficult, given the limitations of current imaging techniques and biomarkers. Moreover, excessive exercise may precipitate cardiac decompensation, arrhythmias, or dysfunction. Future research should therefore prioritize the development of personalized exercise prescriptions, refinement of diagnostic technologies, and elucidation of the molecular mechanisms driving cardiac decompensation. Such efforts will not only deepen the scientific understanding of exercise-related cardiac remodeling but also provide practical guidance for athlete training and cardiovascular disease prevention.